The acceleration and deceleration profiles of elite female soccer players during competitive matches - Mara, J. K.; Thompson, K. G.; Pumpa, K. L.; Morgan, S. (Journal of Science and Medicine in Sport, 2017)
Objectives: The aim of this study was to determine the acceleration (<=-2 m s-2) and deceleration (<= - 2 m s-2) profiles of elite female soccer players during competitive matches. Design: Single cohort, observational study. Methods: An Optical Player Tracking system was used to determine acceleration (>=2 m s-2) and deceleration (>= - 2 m s-2) variables for twelve elite female players across seven competitive matches. Results: In total, players performed 423 (±126) accelerations and 430 (±125) decelerations per match. It was shown that the number of accelerations (p = 0.003-0.034, partial n2 = 0.229-321) and decelerations (p = 0.012-0.031, partial n2 = 0.233-275) at different intensities (based on the start and final velocity) varied according to player position. Mean and maximum distance per effort was 1-4 m and 2-8 m, respectively, and differed between each intensity category (p < 0.001, partial n2 = 0.753-0.908). The mean time between efforts was 14 s for both accelerations (±5 s) and decelerations (±4 s) and fluctuated between 15 min time periods (p<0.001, partial n2 = 0.148-0.206). Conclusions: The acceleration and deceleration profiles varied according to player position and time period of the match. The results of this study can be used to design match-specific acceleration and deceleration drills to enhance change of speed ability.